Cephalometric evaluation of the airway space and hyoid bone in children with normal and atypical deglutition: correlation study - Machado Júnior, Almiro José (2012)
CONTEXT AND OBJECTIVE: Although there is a close relationship between swallowing and breathing, there are no studies evaluating the radiographic anatomy of the airway and its possible correlation with the radiographic position of the hyoid bone. The aim of this study was to evaluate the possible correlation of the radiographic position of the hyoid bone and airway space (PAS) in lateral radiographs on children with atypical deglutition, in comparison with those with normal swallowing. DESIGN AND SETTING: Cross-sectional analytical study with control group in a public university. METHODS: Using cephalometric analysis on lateral teleradiographs, the distance from the hyoid bone to the mandibular plane (MP-H) and the distance from the hyoid bone to the tuber (T-H) were correlated with the PAS measurement (airway) in two groups: 55 teleradiographs in the experimental group (with atypical deglutition) and 55 teleradiographs in the control group (normal deglutition). Both groups included subjects at the mixed dentition stage. RESULTS: The variable T-H presented a statistically significant correlation with PAS (0.0286) and the variable MP-H had a significant correlation with the variable PAS (0.0053). This positive correlation was significant only in the control group and not in the group with atypical swallowing. CONCLUSIONS: There was a positive correlation between the MP-H and PAS measurements and between the T-H and PAS measurements only in the group with normal swallowing. These correlations were not observed in the group with atypical swallowing.